Sustaining teacher education in Nigeria in the ‘new normal’ era (2022)
Covid-19 that started in Wuhan, China in December 2019 that almost every sectors including education. The pandemic did not only disrupt commercial and economic activities. Its‟ also affect education. To ensure that the pandemic did not claim total paralysis of education lead to the adaptation of teaching and learning in the period and tagging the process as new normal of teaching and learning. Students and teachers and distancing themselves from each other, face-to-face teaching was reduced to barest minimum and schools and colleges were under key and locked. This paper therefore explored sustaining teacher education in Nigeria in the new normal era with considerations for deficits in quality of education and provisions for it and sustenance in the new normal and project the nexus between the new normal and teacher education sustainability in Nigeria. Some of the challenges beclouding teacher education were explained and finally the paper proffer what should be done and recommendations.